REMOTE SENSING OF SURFACE HEAT ISLANDS: EXAMPLES OF SMALL- AND MEDIUM - SIZED CITIES IN THE TROPICAL ENVIRONMENT, BRAZIL - Costa Trindade Amorim, Margarete Cristiane de [UNESP] (Univ Lisboa, Fac Letters, Centro Estudos Classicos, 2017)
The purpose of this article is to identify how island surface heat is spatialized in small - and medium - sized cities through the use of images of the thermal infrared channel of the Landsat 8 satellite. It thus intends to assess the characteristics of surface temperatures and the spatial distribution of woody vegetation, construction density and the types of rooftop materials in small - and medium-sized cities in a tropical environment. We diagnosed surface heat islands of strong magnitude (8-11 degrees C), and the areas with the highest temperatures were associated with construction materials used in rooftops, particularly asbestos cement and zinc, construction density and lack of woody vegetation.
Keywords: Urban climate; surface heat island; Landsat 8; remote sensing; tropical cities